Léxico de origem africana no português falado em Luanda - Silva, Josimar Santana (2021)
The present work is the thesis that is the result of a research entitled Lexicon of African origin in Portuguese spoken in Luanda-Angola. Considering the premises that the Portuguese language in Africa, especially in Angola, had contact with the languages ​​that already existed in that region and that, since then, had a change in its lexicon, it was possible to formulate the following study question: what are the lexias that are being used in Angolan Portuguese from African languages? In response to such questioning, the following hypotheses were considered: a) There are African-based lexias in Angolan Portuguese, since the formation of the official language of Angola was constituted by an intense contact with African languages; b) Some lexias of African origins used in Angolan Portuguese have different meanings from those of origin, since contact with the different African languages ​​could have changed the real meanings. This research had, as general objective to inventory the lexias in the African varieties of Portuguese spoken in Luanda-Angola, in order to build a glossary. It also presents the following specific objectives: (i) describe the lexias of African origin present in Angolan Portuguese; (ii) explain the contributions of the lexicon of African origin in the constitution of Angolan Portuguese and (iii) build a glossary with the lexias of African bases found in Portuguese spoken in Luanda-Angola. This study raised the corpus that belongs to the research project “In search of the roots of Brazilian Portuguese: morphosyntactic studies”, based at the Center for Studies in Portuguese Language at the State University of Feira de Santana (NELP / UEFS). The methodology was based on computer programs appropriate for the survey and subsequent verification of the data found for this research, which indicate that the lexicon of African origin present in the interviews is not composed of a large number of lexias, however it responds to the research problem. and prove the hypotheses raised in this thesis. In order to ascertain the data, the lexias recorded in the works of Castro (2001; 2002), Coutinho (2010) and the kimbundu-Portuguese dictionary, organized by Assis Júnior (1947) were considered. The results show that there are lexias present in the Angolan Portuguese, some meanings continue with the traditional senses, but others showed a different meaning, depending on the context in which they are employed. It is expected that this research will offer contributions to the material already elaborated on the theme and, from it, may arouse the interest of new studies about the lexicon of African origin in the Portuguese language.